2022
DOI: 10.3390/electronics11203345
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Characterized Identification of Mono-to-Multi-Layer Graphene and Its Biomedical Applications: A Review

Abstract: The remarkable mechanical, electrical, and thermal capabilities of monolayer graphene make it a wonder substance. As the number of layers in graphene flakes increases to few-layer graphene (number of layers ≤ 5) and multi-layer graphene (number of layers ≤ 10), its properties are affected. In order to obtain the necessary qualities, it is crucial to manage the number of layers in the graphene flake. Therefore, in the current review, we discuss the various processes for producing mono- and few-/multi-layer grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 176 publications
0
18
0
Order By: Relevance
“…However, TEM is more precise when the measurement of CDs exceeds the resolution of SEM, which is within the range of 1–20 nm. This is because TEM affords higher resolving power (~0.2 nm), which is more suitable to identify small-size particles compared to SEM; TEM utilizes high-energy electron beams to transmit through the CD sample to obtain images [ 15 , 109 , 110 ]. For example, an average size of 12 nm of silica-encapsulated CDs and an average size of 0.9 nm of organosilane-synthesized CDs were identified using TEM in a study conducted by Wang and colleagues [ 111 ].…”
Section: Characterization Of Carbon Dotsmentioning
confidence: 99%
“…However, TEM is more precise when the measurement of CDs exceeds the resolution of SEM, which is within the range of 1–20 nm. This is because TEM affords higher resolving power (~0.2 nm), which is more suitable to identify small-size particles compared to SEM; TEM utilizes high-energy electron beams to transmit through the CD sample to obtain images [ 15 , 109 , 110 ]. For example, an average size of 12 nm of silica-encapsulated CDs and an average size of 0.9 nm of organosilane-synthesized CDs were identified using TEM in a study conducted by Wang and colleagues [ 111 ].…”
Section: Characterization Of Carbon Dotsmentioning
confidence: 99%
“…We found that the mechanical properties decreased as the number of layers increased from monolayer to multi-layer graphene. It is clear that the fracture strain and ultimate tensile strength are not significantly affected by the transition from few-layer graphene to multilayer graphene [ 58 ]. For six-layer graphene, it was found that the ultimate tensile strength was 115.6 GPa, and the fracture strain was 0.136 [ 58 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is clear that the fracture strain and ultimate tensile strength are not significantly affected by the transition from few-layer graphene to multilayer graphene [ 58 ]. For six-layer graphene, it was found that the ultimate tensile strength was 115.6 GPa, and the fracture strain was 0.136 [ 58 ]. The difference in strength values can be explained by the absence of defects in the structure in the MD model.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From these, graphene oxide and its derived materials have proved benefit in biological applications, and in recent years, the number of studies looking at graphene and its derivatives as a reinforcing phase in composite coatings has been growing quickly. [136] Apart from these applications, Graphene oxide and its based nanocomposites also have application in biomedical devices like sensor device, nucleic acid sensor device, immune sensor device, cell sensor device, imaging devices, etc.. [164,165,166]…”
Section: Graphene and Its Based Nanocomposites Applications Referencesmentioning
confidence: 99%